2018
DOI: 10.3390/su10103582
|View full text |Cite
|
Sign up to set email alerts
|

Weather and Air Quality Drive the Winter Use of Utah’s Big and Little Cottonwood Canyons

Abstract: Winter outdoor recreation opportunities in Utah are directly impacted by the effects of climate change and deteriorating air quality. We examine the influences of daily weather conditions and air quality on winter use of two prominent Utah canyons located just outside Salt Lake City-Big and Little Cottonwood Canyons. Daily weather data were collected both within the canyons and in Salt Lake City; daily air quality data were collected for just Salt Lake City. We hypothesized that desirable weather within the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These results suggest that while trail users value clean air, they may not consciously consider this factor when deciding whether to recreate on the ERT. In light of similar previous research [37], it is possible that expectancy-valence theory (operationalized as PHORS in this study) is a superior predictor of recreation choices compared to experiential models. Another possibility is that experiential benefits are subsumed within valence, with varying degrees of salience to the recreationist [14,32].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…These results suggest that while trail users value clean air, they may not consciously consider this factor when deciding whether to recreate on the ERT. In light of similar previous research [37], it is possible that expectancy-valence theory (operationalized as PHORS in this study) is a superior predictor of recreation choices compared to experiential models. Another possibility is that experiential benefits are subsumed within valence, with varying degrees of salience to the recreationist [14,32].…”
Section: Discussionmentioning
confidence: 51%
“…Dann defined push factors as personal preferences, whereas pull factors are attributes of the recreation site [33]. These factors, such as weather and PM [37], are suggested to determine travel and recreation site choices. A different approach, proposed by Driver, focuses on experiential factors linked to desired outcomes [34].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These activities are all sensitive to temperature, snowfall, and snow depth. Contrary to general park visitation and fishing, for snow-based activities, higher temperatures were correlated with lower visitation numbers [78][79][80][81]. This is likely because higher temperatures correlate to lower snowfall and snow depth.…”
Section: Snow-based Recreationmentioning
confidence: 88%
“…with cash flow at a resort [82], and that snow depth is positively related to daily ticket sales at resorts [80]. For general snow-based recreation (including but not limited to downhill skiing), one study found daily snow depth was positively related to visitation, but daily snowfall was not significant [78]. Generally, snowfall seemed to be significant at larger scales (e.g., months or seasons), but less influential than snow depth on a daily scale.…”
Section: Plos Climatementioning
confidence: 99%